Impact of selected social welfare programs on poverty alleviation and health outcomes in Pakistan (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2021)
The purpose of this paper is to review and analyse poverty alleviation and health outcomes through the effectiveness of two major programs launched by the government to uplift social welfare in Pakistan (Benazir Income Support Program (BISP) and the Sehat Sahulat Program (SSP). We also aim to explore the link between poverty and health in light of the BISP and SSP. Secondary data is utilized to carry out this study, where qualitative data is gathered from the beneficiaries’ interviews while quantitative data is based upon the poverty line. Through this study, we can conclude an overall positive impact of the BISP and SSP on two components of the Human Development Indicator (HDI) concerning poverty and health: standards of living and life expectancy. Although positive conclusions have been brought about by BISP such as a reduction in wasting (girls) and increased food consumption, it fails to substantially cover health and may even be ineffective if individuals face external shocks such as dangerous illnesses. Such findings strengthen the importance of the SSP as a social welfare program alongside the BISP to secure far more wholesome and successful outcomes. By exploring the interchangeable link between poverty and health and connecting it to these programs, we further assert the complimentary nature of the BISP and SSP and base our evaluation on it.